Cost-effectiveness analysis of mesh fixation techniques for laparoscopic and open inguinal hernia surgeries - Suphakarn Techapongsatorn; Amarit Tansawet; Oraluck Pattanaprateep; John Attia; Gareth J. Mckay; Ammarin Thakkinstian (BMC, 2022)
Abstract Purpose This study reports economic evaluation of mesh fixation in open and laparoscopic hernia repair from a prospective real-world cohort study, using cost-effectiveness analysis (CEA) and cost-utility analysis (CUA). Methods A prospective real-world cohort study was conducted in two university-based hospitals in Thailand from November 2018 to 2019. Patient data on hernia features, operative approaches, clinical outcomes, associated cost data, and quality of life were collected. Models were used to determine each group's treatment effect, potential outcome means, and average treatment effects. An incremental cost-effectiveness ratio was used to evaluate the incremental risk of hernia recurrences. Results The 261 patients in this study were divided into six groups: laparoscopic with tack (LT, n = 47), glue (LG, n = 26), and self-gripping mesh (LSG, n = 30), and open with suture (OS, n = 117), glue (OG, n = 18), and self-gripping mesh (OSG, n = 23). Hernia recurrence was most common in LSG. The mean utility score was highest in OG and OSG (both 0.99). Treatment costs were generally higher for laparoscopic than open procedures. The cost-effectiveness plane for utility and hernia recurrence identified LSG as least cost effective. Cost-effectiveness acceptability curves identified OG as having the highest probability of being cost effective at willingness to pay levels between $0 and $3,300, followed by OSG. Conclusion Given the similarity of hernia recurrence among all major procedures, the cost of surgery may impact the decision. According to our findings, open hernia repair with adhesive or self-gripping mesh appears most cost-effective.